Evaluation of race and ethnicity disparities in outcome studies of CYP2C19 genotype-guided antiplatelet therapy - Nguyen, Anh B.; Cavallari, Larisa H.; Rossi, Joseph S.; Stouffer, George A.; Lee, Craig R. (Frontiers in Cardiovascular Medicine, 2022)
Dual antiplatelet therapy with a P2Y12 inhibitor (clopidogrel, prasugrel, or ticagrelor) and aspirin remains the standard of care for all patients undergoing percutaneous coronary intervention (PCI). It is well-established that patients carrying CYP2C19 no function alleles have impaired capacity to convert clopidogrel into its active metabolite and thus, are at higher risk of major adverse cardiovascular events (MACE). The metabolism and clinical effectiveness of prasugrel and ticagrelor are not affected by CYP2C19 genotype, and accumulating evidence from multiple randomized and observational studies demonstrates that CYP2C19 genotype-guided antiplatelet therapy following PCI improves clinical outcomes. However, most antiplatelet pharmacogenomic outcome studies to date have lacked racial and ethnic diversity. In this review, we will (1) summarize current guideline recommendations and clinical outcome evidence related to CYP2C19 genotype-guided antiplatelet therapy, (2) evaluate the presence of potential racial and ethnic disparities in the major outcome studies supporting current genotype-guided antiplatelet therapy recommendations, and (3) identify remaining knowledge gaps and future research directions necessary to advance implementation of this precision medicine strategy for dual antiplatelet therapy in diverse, real-world clinical settings.